Przygotowanie i dziękczynienie (kan. 909 KPK) - Kazimierz Dullak (Colloquia Theologica Ottoniana, 2013)
Canon 909 CIC in a concise, yet suggestive indicates the need for proper preparation by prayer to celebrate the Eucharist, and then make a thanksgiving to God for the salvation events taking place here and now, during the celebration of the Holy Sacrifice. Pastors of the Church in Poland suggest that the next private prayer language should be restraint leads to focus on in silence. Event Saints good experience also serves as a prior preparation of the liturgy of the spatial (space liturgical design) and limited (singing, people associated with the service of the liturgy). The preparation phase is the celebrant himself as well as all the participants in the liturgy. This eventually leads to gratitude to God manifested in an attitude of thanksgiving at the end of the liturgical celebrations.